Road Speed Profile: A Case Study of Pracha Uthit Road - Putthajernjitt, Anapat; Sriyotha, Kanokwan; Thippaway , Satreerat; Kiattikomol, Vasin; Jutipanya, Kelwalee (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
The objective of this research is to study the speed profile of Pracha Uthit Road from Pracha Uthit Intersection to Na Luang Intersection in order to understand traffic conditions along the study corridor. Heat maps were created to identify the locations and time periods with traffic congestion. The data used for this study were obtained from Thai Intelligent Traffic Information Center (iTIC), which include the information from the Global Positioning System (GPS) equipment installed on public taxis. From the analysis results, it is found that the traffic congestion pattern throughout the corridor changed according to the time of day where there was recurring congestion at some locations. The speed profiles obtained from this research can be used to pinpoint roadway bottlenecks and apply proper mitigation measures for the roadway sections such as a reversible lane strategy. Knowing the speed profile allows one to efficiently determine the operational boundary as well as the operational time of the managed lane application. The method used in this study can be used to assess roadway speed profiles as a tool to help decision-makers effectively solve traffic congestion problems in a road network.